Inflammation‐based scores do not predict post‐transplant recurrence of hepatocellular carcinoma in patients within milan criteria. Issue 11 (November 2014) - Parisi, Ioanna; Tsochatzis, Emmanuel; Wijewantha, Hasitha; Rodríguez‐Perálvarez, Manuel; Luca, Laura De; Manousou, Pinelopi; Fatourou, Evangelia; Pieri, Giulia; Papastergiou, Vassilios; Davies, Neil; Yu, Dominic; Luong, TuVinh; et al.
<x xml:space="preserve">Abstract</x> Increased preoperative inflammation scores, such as neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR) and inflammation‐based index (IBI) have been related to post‐transplant HCC recurrence. We evaluated the association between inflammation‐based scores (NLR, PLR, IBI) and post‐LT HCC recurrence as well as tumor necrosis after transarterial embolization. 150 consecutive patients who underwent transplantation for HCC within the Milan criteria between 1996 and 2010 were included; data regarding inflammatory markers, patient and tumor characteristics were analyzed. NLR, PLR, and IBI were not significantly associated with post‐LT HCC recurrence or worse overall survival. Increased NLR and PLR were associated with complete tumor necrosis in the subset of patients who received preoperative transarterial embolization (P < 0.05). Cox regression analysis revealed that absence of neoadjuvant transarterial therapy (OR = 4.33, 95% CI = 1.28‐14.64; P = 0.02) and no fulfillment of the Milan criteria in the explanted liver (OR = 3.34, 95% CI = 1.08‐10.35; P = 0.04) were independently associated with post‐LT HCC recurrence inflammation‐based scores did not predict HCC recurrence post‐LT in our group of patients. NLR and PLR were associated with better response to TAE, as this was recorded histologically in the explanted liver. Histological fulfillment of the Milan criteria and absence of neoadjuvant transarterial treatment were significantly associated with post‐LT HCC recurrence. Liver Transpl 20:1327‐1335, 2014. © 2014 AASLD.